Świadomość ubezpieczeniowa przedsiębiorców w zakresie ubezpieczenia należności - Dankiewicz, Robert (Insurance's Awareness of Entrepreneurs in Respect to Insured Dues, 2008)
In the article, the author tries to evaluate the insurance's awareness of entrepreneurs, attaching particular importance to the insured dues. He focuses on the factors shaping awareness and importance of the insurer. Because of its specific nature, the evaluation of insurance's awareness, in case of insured dues, should be lead in areas like: awareness of product occurrence in the market, scope of services offered by insurers, and terms of insurance. The conclusions which were drawn allow to make a statement that the process of insurance awareness increases, but very often it has selective character.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 62-68